BIBLIOMETRIC ANALYSIS OF CHICKEN BONE PROCESSING AS ANTI-AGING ON SKIN THROUGH VOSVIEWER APPLICATION - Farras Khirzi Khanifah (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2023)
This study aims to determine the number of scientific publications on chicken bone processing as an anti-aging agent using bibliometric analysis, which can determine the researched areas to provide an overview of the latest research developments, trends, and future projections related to chicken bone waste processing as an anti-aging material on the skin. The study was conducted by using a qualitative literature review method through the Scopus web. The data obtained were 13 articles within the period of 2013-2023, and data analysis was performed using the VOSviewer application. The research results showed that the number of occurrences and total link strength is most arranged from the cluster with the keywords collagen, chicken feet, gelatine, SDS-page, FTR. Acid solubilized collagen. The overlay visualization results indicated that the most current keywords are FTIR. Acid solubilized collagen and SDS page. For the keywords gelatine, SDS-page, and black-bone chicken, they are still under-researched and can be used as a reference or idea for further research. This study is still limited to the database coverage with one source, namely the Scopus web, so it did not have comparative data.